Paradigma Integrated Twin Towers dalam Studi Hubungan Internasional Kontemporer - Hakim, Moh. Fathoni (Journal of Integrative International Relations, 2017)
Integrated Twin Towers paradigm that is embraced by UIN Sunan Ampel Surabaya stresses on the relation between science and social knowledge with Islamic knowledge which are not being overlapped, but are complementing. Paradigmatic discussion of contemporary international relations study offers an opportunity for Integrated Twin Towers paradigm to fulfill a paradigmatic limitedness within such study, especially for alternatives on Islamic knowledge. The International Relations Department in UIN Sunan Ampel Surabaya gives some offerings in translating Integrated Twin Towers paradigm at the smallest level of university. First, creating some courses that consist of Islamic study. Second, preparing for (regulations of) student research. Third, integration between student competency program with Islamic values, such as character building.